2017
DOI: 10.1515/prilozi-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Based Practice in Using Antibiotics for Acute Tonsillitis in Primary Care Practice

Abstract: The increased use of antibiotics for acute tonsillitis is a public health problem. 80% of the antibiotic prescriptions for acute tonsillitis are done in the Primary Care practice (PCP). The inappropriate use of the antibiotic causes bacterial resistance and treatment failure. Only patients with acute tonsillitis caused by Group A beta-hemolytic streptococcus (GAS) have benefit of the antibiotic treatment, which is a predict cause in 5-20%. In order to assess the antibiotic prescribing for acute tonsillitis by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Therefore, there is a need for equilibrium between appropriate usage of antibiotics and access to antibiotics, both of which are complementary to each other [9]. Studies show 75% of antibiotic prescriptions take place in primary care settings [10], and 80% of acute tonsillitis cases are treated with antibiotics in primary care settings [11]. Most inappropriate prescriptions of antibiotics are reported while treating URTIs, and they account for between 30% and 60% [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a need for equilibrium between appropriate usage of antibiotics and access to antibiotics, both of which are complementary to each other [9]. Studies show 75% of antibiotic prescriptions take place in primary care settings [10], and 80% of acute tonsillitis cases are treated with antibiotics in primary care settings [11]. Most inappropriate prescriptions of antibiotics are reported while treating URTIs, and they account for between 30% and 60% [4].…”
Section: Introductionmentioning
confidence: 99%
“…There is scarce published research with regard to suboptimal prescribing in the Western Balkan countries, either in hospital settings, nursing homes, or focused on specific drug groups like benzodiazepines and antibiotics. 8 - 13 Only few studies have reported inappropriate prescribing in primary care among older patients of the Western Balkans, and just one in Albania, a middle-income country. 14 - 17…”
Section: Introductionmentioning
confidence: 99%
“…6,7 There is scarce published research with regard to suboptimal prescribing in the Western Balkan countries, either in hospital settings, nursing homes, or focused on specific drug groups like benzodiazepines and antibiotics. [8][9][10][11][12][13] Only few studies have reported inappropriate prescribing in primary care among older patients of the Western Balkans, and just one in Albania, a middle-income country. [14][15][16][17] Obviously, in order to design and implement effective interventions to reduce improper prescribing, measuring the extent and factors related to this issue is essential.…”
Section: Introductionmentioning
confidence: 99%